Towards Unveiling the Exact Molecular Structure of Amorphous Red Phosphorus by Single‐Molecule Studies - Zhang, Song; Qian, Hu‐jun; Liu, Zhonghua; Ju, Hongyu; Lu, Zhong‐yuan; Zhang, Haiming; Chi, Lifeng; Cui, Shuxun (Angewandte Chemie International Edition, 2019)
Since the discovery of amorphous red phosphorus (a‐red P) in 1847, many possible structures have been proposed. However, the exact molecular structure has not yet been determined because of its amorphous nature. Herein several methods are used to investigate basic properties of a‐red P. Data from scanning tunneling microscopy (STM) and gel permeation chromatography (GPC) confirm that a‐red P is a linear inorganic polymer with a broad molecular weight distribution. The theoretical single‐molecule elasticities of the possible a‐red P structures are obtained by quantum mechanical (QM) calculations. The experimental single‐molecule elasticity of a‐red P measured by single‐molecule AFM matches with the theoretical result of the zig‐zag ladder structure, indicating that a‐red P may adopt this structure. Although this conclusion needs further validation, this fundamental study represents progress towards solving the structure of a‐red P. It is expected that the strategy utilized in this work can be applied to study other inorganic polymers. Zig‐zag: Although amorphous red phosphorus (a‐red P) was discovered for more than 170 years, its exact molecular structure is unknown because of its amorphous nature. Results from single‐molecule AFM, quantum mechanical calculations, and scanning tunneling microscopy suggest that a‐red P may adopt a zig‐zag ladder structure (2 in Scheme).